A Philosophical Analysis of the Principle of Justice in Judicial Decisions in Indonesia - Christopher Elia Julio; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the philosophical foundation of justice as a legal principle in judicial decisions in Indonesia. Using a normative juridical research method, this paper examines the alignment between judicial considerations and the philosophical conception of justice proposed by thinkers such as Aristotle, John Rawls, and Gustav Radbruch. The analysis is based on a literature review of laws, legal doctrines, and selected court decisions that reflect the application of justice as a guiding principle in judicial reasoning. The results show that the philosophical meaning of justice has not been fully realized in every judicial decision, as some judgments still emphasize legal certainty over fairness and moral substance. Therefore, strengthening the philosophical awareness of judges is essential to harmonize justice, certainty, and expediency in Indonesia’s legal system.